Edukasi Sehat Tentang Pencegahan Obesitas Siswa Di Sekolah Dasar - Dwi Setiowati; Kustati Budi Lestari; Irma Nurbaeti; Maulina Handayani (LPPI UMN AL WASHLIYAH, 2025)
Obesity in school-age children is an increasing health problem that has a long-term impact on children's physical and mental conditions. One effective prevention strategy is through early health education in the school environment. This community service activity aims to increase elementary school students' knowledge about obesity prevention through interactive and fun health education. The activity was carried out at SDN 02 Pamulang, South Tangerang, involving 140 5th grade students, four lecturers, and 14 nursing students. The methods used included anthropometric measurements (height and weight), educational game “Isi Piringku”, counseling using poster media, as well as pre-test and post-test. The results of the activity showed an increase in students' enthusiasm and knowledge of the importance of balanced nutrition and physical activity as an effort to prevent obesity. This activity also received full support from the school and teachers. As a follow-up, monitoring student health through the School Health Unit (UKS) is recommended to be carried out regularly to maintain the results that have been achieved. Strengthening the role of schools as an educational environment in the promotion of healthy lifestyles is key in efforts to prevent obesity from an early age. Keywords: childhood obesity, health education, balanced nutrition